The external sector of the Serbian economy - Ristanović Vladimir (Trendovi u Poslovanju)
The aim of this paper is to show the external sector of the Serbian economy, its features and peculiarities, as well as anomalies that afflicted it for years. In the analysis, data acquired from the Statistical Office of the Republic of Serbia will be used, as well as the official international methodology. The text will include the analysis of the structure of the external sector, market share, competitive position of Serbian economy and export products according to sectors of the economy and factor intensity. Since 2000, the structure of production and exports of the Serbian economy shows low comparative advantages and competitive position throughout the world. Unfavorable structure of the sectors, departments and the product groups affected the deepening of external imbalances and high foreign trade deficit. Exports of technology of predominantly low intensity, resources, and labor-intensive products, common for Serbian economy, represent no guarantee of economic growth in the long term. The causes of external imbalances should be sought in the absence of adequate export strategy, as well as in high speed of liberalization of foreign trade flows and exchange rate policy.